2019
DOI: 10.1063/1.5090444
|View full text |Cite
|
Sign up to set email alerts
|

Antiferroelectric order and Ta-doped AgNbO3 with higher energy storage density

Abstract: Antiferroelectric phenomenological theory can well depict the behavior of the antiferroelectric system, but how to quantitatively define the antiferroelectric order parameter based on the experimental results is still an open question. In this work, the reduced antiferroelectric order parameter is proposed based on the direct atomic-scale observation, which can be regarded as an extension of the traditional antiferroelectric order parameter. In addition, the enhancement of energy storage density of Ta-doped si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In AgNbO 3 , the polarity switching process is accomplished by Nb 5+ ions shifting within the equatorial plane ( ab plane) of NbO 6 octahedra (it should be noted that the shifting of Ag ions may also contribute to the polarization but is more complex) . Obviously, the polarization induced by this displacement is proportional to the effective charge and the displacement of the individual ion . As the ion displacement is constrained by rare-earth element doping, the contribution of the displacement to the total polarization will be limited, leading to decreased polarization of the ferroelectric phase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In AgNbO 3 , the polarity switching process is accomplished by Nb 5+ ions shifting within the equatorial plane ( ab plane) of NbO 6 octahedra (it should be noted that the shifting of Ag ions may also contribute to the polarization but is more complex) . Obviously, the polarization induced by this displacement is proportional to the effective charge and the displacement of the individual ion . As the ion displacement is constrained by rare-earth element doping, the contribution of the displacement to the total polarization will be limited, leading to decreased polarization of the ferroelectric phase.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretically, E A and E F are larger than E 0 ; thus, an increased E 0 leads to increased E A and E F . A reasonable approximation of the critical electric field can be written as where η 0 is the antiferroelectric order parameter under zero electric field and χ 0 is the dielectric susceptibility (χ = ε r – 1, ε r is the relative dielectric permittivity as given in Figure a). It is clear that E 0 is inversely proportional to χ 0 3/2 , therefore, the critical electric field E 0 can be increased by decreasing the dielectric constant of the paraelectric phase or by increasing the antiferroelectric order parameter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The niobate perovskites NaNbO 3 and AgNbO 3 have polar structures at room temperature and have been identified as promising lead-free replacements for the piezoelectric material PbZr 1– x Ti x O 3 (PZT) . Ceramics based on AgNbO 3 also show great potential as lead-free candidates for dielectric energy-storage applications. The niobate perovskites are structurally complex as exemplified by NaNbO 3 , which shows a baffling array of temperature-dependent structural phase transitions. High-resolution neutron diffraction studies have revealed the structural sequence in NaNbO 3 upon heating to be R 3 c → Pbcm → Pmmn → Pmmn → Cmcm → P 4/ mbm → Pm 3̅ m . , This sequence of phases is often described using the notation developed by Megaw as N → P → R → S → T 1 → T 2 → U . There is evidence that at room temperature a second orthorhombic phase in space group P 2 1 ma can coexist with the Pbcm (an alternate setting of Pcam ) phase of NaNbO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…[3] There are many different strategies to improve the energy storage performance of ferroic materials. [4][5][6] A comprehensive studies trying to modify or reshape the hysteresis loop for larger storage capacity have been demonstrated through A-site doping, [7][8][9][10][11][12] B-site doping [13,14] and simultaneously doping both sites. [15] However, there exists nontrivial and critical debates about the crystalline structure of ANO at room temperature.…”
mentioning
confidence: 99%